Evaluation of nurses' performance and knowledge of the correct method of disinfection of consumables and consumables in endoscopy departments of covered hospitals Mashhad University of Medical Sciences - Shapour Badiee; Behnaz Samiee; Golnaz Sabouri; Elnaz Sadeghian; Zahra Abbasi Shaye; Javad Mahmoudi Fathabadi; Rozita Davoodi; Fariba Zeinaly; Negaer Yeganeh Khorasani (Patient Safety and Quality Improvement Journal)
Introduction:The increase and diversity of diagnostic and therapeutic methods using rigid or flexible endoscopes have focused much attention on the possibility of infection transmission in this way. Therefore, nursing personnel must have basic information on sterilization and disinfection of tools.Materials and Methods:This descriptive-analytical study aimed to evaluate the staff’s performance and awareness of healthcare instructions for proper disinfection of endoscopic consumable and non-consumption equipment in the hospital affiliated with Mashhad University of Medical Sciences, which had endoscopy departments. The data collection tool was the standard endoscope decontamination evaluation checklist taken from the translation of the checklist of WHO and analyzed by SPSS 20 statistical software.Results: The results showed a statistically significant difference between nurses' knowledge and performance (P-value = 0.03), and nurses' performance had lower percentages than knowledge.Conclusion:Due to the statistically significant difference in nurses' knowledge and practice in correct disinfection of consumable and non-consumable equipment in endoscopy and the low performance of nurses in some areas of the disinfection process, interventions such as face-to-face training of nurses and continuous monitoring of performance, especially evaluation of three months of nurses' performance are necessary.